Une Mécanisation Appropriée à l’Echelle de L’Exploitation Peut Contribuer à la Transition Agroécologique - Idoudi, Zied (International Center for Agricultural Research in the Dry Areas, 2024)
This presentation was made during a side event entitled "Agroecology as a solution for climate-resilient agriculture", held in Bizerte, Tunisia, on 4-5 May. The event was part of the Agroecology Convergence Days organised by the Tunisian Network for Agroecological Transition. It featured keynote presentations from ICARDA and its Agroecology Team, which is part of the CGIAR Research Initiative on Agroecology. The presentation focused on the role of appropriate mechanization in supporting agroecological practices and facilitating the transition to sustainable local food systems, while addressing the challenges of climate resilience in the region. Participants included a wide range of stakeholders, including civil society representatives, policy makers, practitioners, farmers, national and international experts, extension workers and researchers. A total of 80 participants attended, with women representing 50% of the participants.